Inequalities and Indirect Conflict Interventions: The Evidence on Perceptions of Difference, Social Cohesion, and Sub-national Variations in Violence in Central Sulawesi, Indonesia - Rachael Diprose (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2009)
This paper examines the empirical evidence on social cohesion and perceived horizontal inequalities in two neighbouring districts in Central Sulawesi, Indonesia. Despite having similar sized groups (religiously polarised, ethnically fragmented) and the opportunity to mobilise during the national political transition beginning in 1998, only one of the districts had serious violence. First, the evidence suggests that such violence was linked to perceived horizontal inequalities in terms of access to the state, particularly in terms of religious identity in the district affected by con?ict. In the same district, there was also evidence of weaker social cohesion: there were more pervasive negative stereotypes of other groups along religious lines, and the least inter-religious mixing in terms of everyday interaction and friendships. These attitudes and less frequent mixing were more likely, too, among the group that was initially marginalised from the state when power-sharing arrangements broke down. Meanwhile, in the district with less violence, there was more frequent inter-religious group mixing overall but particularly on the part of the group that did not dominate the state. That is, frequent inter-religious group mixing and the absence of negative attitudes on the part of this group towards others may have signalled that it was not a viable group to be mobilised for political gain. Instead, in this more peaceful district, ethnic identity was the more salient form of political capital, but demographically the district is ethnically fragmented. Inter-ethnic rather than religious mixing was less frequent in this district, but it was worst among the dominant political group along religious and ethnic lines. Yet, the negative attitudes and stronger in-group (rather than out-group) bonds between members of the dominant political group did not translate into violent con?ict because there were minimal challenges to their power during the transition. Finally, the evidence suggests that the associational membership of mixedethnic or religious organisations is less likely to explain violence prevention, given that membership of such organisations was greater in the con?ict-affected district. The evidence overall suggests that demographic divides are not always an indicator of political divides and the propensity for con?ict, but rather this is related to the politics of exclusion. Furthermore, it indicates that to some extent increased crossgroup contact can act as an indirect con?ict intervention mechanism.